2005
DOI: 10.1021/ja051653o
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructuring, Compositional Fluctuations, and Atomic Ordering in the Thermoelectric Materials AgPbmSbTe2+m. The Myth of Solid Solutions

Abstract: The nature of the thermoelectric materials Ag(1-x)Pb(m)SbTe(m+2) or LAST-m materials (LAST for Lead Antimony Silver Tellurium) with different m values at the atomic as well as nanoscale was studied with powder/single-crystal X-ray diffraction, electron diffraction, and high-resolution transmission electron microscopy. Powder diffraction patterns of different members (m = 0, 6, 12, 18, infinity) are consistent with pure phases crystallizing in the NaCl-structure-type (Fmm) and the proposition that the LAST fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
228
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 354 publications
(258 citation statements)
references
References 30 publications
27
228
1
2
Order By: Relevance
“…Many studies have been carried out on the LAST system by Kanatzidis's group, particularly with respect to microstructure characterization [66] and exploration of p-type LAST systems [67][68][69]. Th ey have found that a high ZT value of 1.45 at 630 K is achievable in p-type Ag(Pb 1-x Sn x ) m SbTe 2+m by partially substituting the lead in the LAST system with tin [67].…”
Section: Cosb 3 -Based Skutteruditesmentioning
confidence: 99%
“…Many studies have been carried out on the LAST system by Kanatzidis's group, particularly with respect to microstructure characterization [66] and exploration of p-type LAST systems [67][68][69]. Th ey have found that a high ZT value of 1.45 at 630 K is achievable in p-type Ag(Pb 1-x Sn x ) m SbTe 2+m by partially substituting the lead in the LAST system with tin [67].…”
Section: Cosb 3 -Based Skutteruditesmentioning
confidence: 99%
“…‡ Crystal structures with symmetry less than Fm 3m (Pm 3m, P4/mmm, or R 3m) have been proposed by Quarez. 17 The crystal structure data based on the space group Fm 3m are still useful for the purposes of phase identification and clarification of the orientation relationship.…”
Section: 34mentioning
confidence: 99%
“…5 An interesting possibility is that these nanoclusters are key components in the ZT enhancement. The HRTEM images show the clusters are randomly distributed through the matrix and are not long-range ordered.…”
Section: Introductionmentioning
confidence: 99%